ANALISIS DAYA SAING DAN DETERMINAN EKSPOR TEKSTIL DAN PRODUK TEKSTIL (TPT) INDONESIA - Shita; Nyoman Reni Suasih, Ni (Universitas Pasundan, 2025)
Indonesia, as a country that is quite active in international trade, has several leading export sectors to increase its national income. One of the main pillars of Indonesian exports is the processing industry. The textile and textile product (TPT) industry is one of the pioneer industries and the backbone of the processing industry in Indonesia. This industry is one of the priority and mainstay industries that will be developed. During the 2010-2019 period, developments in the value of Indonesian TPT exports tended to fluctuate. The decline in global demand coupled with increasingly tight competition in the international market has resulted in Indonesia's TPT export performance continuing to weaken. The aim of this research is to analyze the competitiveness and determinants of Indonesian TPT exports. This research is quantitative research. Data collection was obtained through the Central Statistics Agency (BPS), World Integrated Trade Solution (WITS), World Bank, Ministry of Industry, and the Directorate General of Plantations, Ministry of Agriculture of the Republic of Indonesia, which was then analyzed using the Revealed Comparative Advantage (RCA) method to measure the level of competitiveness and Error Correction Model (ECM) to determine short-term and long-term effects. The research results show that based on the RCA estimation results, it can be seen that Indonesia has comparative advantage in TPT commodities globally. Based on the results of the ECM analysis, Indonesian TPT exports, foreign direct investment, exchange rates, inflation, world economic growth and cotton imports are cointegrated so that there is a relationship in the short and long term.